2020
DOI: 10.1371/journal.pcbi.1007693
|View full text |Cite
|
Sign up to set email alerts
|

Tensile force-induced cytoskeletal remodeling: Mechanics before chemistry

Abstract: Understanding cellular remodeling in response to mechanical stimuli is a critical step in elucidating mechanical activation of biochemical signaling pathways. Experimental evidence indicates that external stress-induced subcellular adaptation is accomplished through dynamic cytoskeletal reorganization. To study the interactions between subcellular structures involved in transducing mechanical signals, we combined experimental data and computational simulations to evaluate real-time mechanical adaptation of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…Using MEDYAN, we performed simulations of small cytoskeletal networks consisting of 50 actin filaments in 1- hard-walled cubic boxes with varying concentrations of -actinin cross-linkers ( ) and of NMIIA myosin-motor minifilaments ( ) ( 13 , 20 , 31 33 ). We omit here other associated proteins, such as the branching agent Arp2/3, finding that our minimal system is sufficient to produce heavy-tailed distributions of event sizes, although it has recently been discovered that branching acts to enhance avalanche-like processes ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using MEDYAN, we performed simulations of small cytoskeletal networks consisting of 50 actin filaments in 1- hard-walled cubic boxes with varying concentrations of -actinin cross-linkers ( ) and of NMIIA myosin-motor minifilaments ( ) ( 13 , 20 , 31 33 ). We omit here other associated proteins, such as the branching agent Arp2/3, finding that our minimal system is sufficient to produce heavy-tailed distributions of event sizes, although it has recently been discovered that branching acts to enhance avalanche-like processes ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…One can ask if by tuning the strength of this or other cytoquake-modulating factors, the network is more or less responsive to external perturbation. This perturbation could be introduced either mechanically, for example, through a simulated or real-force microscopy experiment, or chemically, through a variation of the chemical boundary conditions ( 33 ). Such studies should clarify whether large events in cytoskeletal dynamics serve a biologically useful purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon mechanical loading, ASMCs reorganise their actin cytoskeleton via a two-step response. Seconds after a force is applied, actin filaments are stretched and align along the direction of the force (Li et al 2020 ). A few minutes later, actin filaments become stabilised through the ATP-dependent process of αSMA crosslinking.…”
Section: Actin Filaments—more Than Just a Contractile Apparatusmentioning
confidence: 99%
“…A recent study [87] also used microscopic Brownian dynamics simulations to show that the observed local maximum in the viscous modulus [47] corresponds to a maximum in CL binding and unbinding events, implying that maximum dissipation occurs when the CL unbinding timescale matches the timescale of the imposed deformation. There have also been a number of computational studies on the structure and contractile behavior of actomyosin networks, which show that a critical concentration of α -actinin cross-linkers can combine with myosin motors to form ordered bundles of actin filaments with varying polarity [69, 45].…”
Section: Introductionmentioning
confidence: 99%